Eye size and shape in newborn children and their relation to axial length and refraction at 3 years. (10th May 2015) - Lim, Laurence Shen; Chua, Sharon; Tan, Pei Ting; Cai, Shirong; Chong, Yap‐Seng; Kwek, Kenneth; Gluckman, Peter D.; Fortier, Marielle V.; Ngo, Cheryl; Qiu, Anqi; Saw, Seang‐Mei
Abstract Purpose To determine if eye size and shape at birth are associated with eye size and refractive error 3 years later. Methods A subset of 173 full‐term newborn infants from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) birth cohort underwent magnetic resonance imaging (MRI) to measure the dimensions of the internal eye. Eye shape was assessed by an oblateness index, calculated as 1 − (axial length/width) or 1 − (axial length/height). Cycloplegic autorefraction (Canon Autorefractor RK‐F1) and optical biometry (IOLMaster) were performed 3 years later. Results Both eyes of 173 children were analysed. Eyes with longer axial length at birth had smaller increases in axial length at 3 years (p < 0.001). Eyes with larger baseline volumes and surface areas had smaller increases in axial length at 3 years (p < 0.001 for both). Eyes which were more oblate at birth had greater increases in axial length at 3 years (p < 0.001). Using width to calculate oblateness, prolate eyes had smaller increases in axial length at 3 years compared to oblate eyes (p < 0.001), and, using height, prolate and spherical eyes had smaller increases in axial length at 3 years compared to oblate eyes (p < 0.001 for both). There were no associations between eye size and shape at birth and refraction, corneal curvature or myopia at 3 years. Conclusions Eyes that are larger and have prolate or spherical shapes at birth exhibit smaller increases in axial length over the first 3 years of life. Eye size and shape at birth influence subsequent eye growth but not refractive error development.